Hukum Sponsorship Bersyarat Online Shop Buynana Chips Perspektif Fikih Muamalah - Nuraeni Novira; Sri Ujiana Putri; Anisa Indarwati Legimin (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
This research aims to determine the concept of conditional sponsorship cooperation in the Buynana Chips online shop and what the law is from a muamalah jurisprudence perspective. The formulation of the problem in this research is: first, what is the concept of conditional sponsorship activities in the Buynana Chips online shop; second, what is the legal review from the perspective of muamalah jurisprudence regarding conditional sponsorship activities at the Buynana Chips online shop. The type of research used is qualitative research, which focuses on field studies. Data collection was carried out by means of observation, interviews and documentation using normative and empirical approach methods. The research results found were as follows: first, the Buynana Chips online shop added several conditions to the sponsorship collaboration, including having to sell a certain amount of its products within two weeks and wages given only based on the number of products sold. The sponsor recipient must also bear the cost of shipping the goods. However, Buynana Chips usually bears a small portion of the shipping costs for the goods to be sent to the sponsor recipient. Fines if you are late in depositing funds to Buynana Chips and penalties for not depositing funds. Second, the conditional sponsorship law in the Buynana Chips online shop is permitted because the conditions are in line with the purpose of the contract, it is a community habit, there are benefits and there is also no coercion in this transaction. Except for the terms of fines which can result in usury transactions